(untitled) (Journal of Nepal Physical Society, 2021)
This paper presents an analysis of the spin vector orientations of SDSS (Sloan Digital Sky Survey) galaxies in the Supercluster S [195+027+0022] using the seventh data release (2008 October). By using the spectroscopic database of galaxies, identified number density map in the region of Superclusters. Several density enhancements are observed, suggesting the possibility of substructure in the Supercluster. Two-dimensional observed parameters that we received from the database are used to compute three-dimensional galaxy rotation axes by applying `position angle-inclination’ method. Apply the selection effects by performing the random simulation method. The expected distribution curves are obtained from the simulation. Chi-square, auto-correlation, and Fourier tests are used to examine non-random effects in the polar and azimuthal angle distributions of the galaxy rotation axes. To check these results with the different galaxy evolution models namely Hierarchy, Primordial, and Pancake model. The result supports the Hierarchy model.